Conversion of primary liver cancer after targeted therapy for liver cancer combined with AFP-targeted CAR T-cell therapy: a case report - Wang, Yun; Zhao, Yan; Li, Miaoling; Hou, Huilian; Jian, Zhijie; Li, Weizhi; Li, Peijie; Ma, Fuquan; Liu, Mengying; Liu, Haibo; Xue, Hui (Frontiers in Immunology, 2023)
Primary liver cancer (PLC) that originates in the liver is a malignant tumor with the worst prognosis. Hepatocellular carcinoma (HCC) is the most common type of PLC. Most PLC cases are diagnosed at advanced stages mainly due to their insidious onset and rapid progression. Patients with PLC undergo surgical intervention or localized treatment, but their survival is often affected by its high relapse rate. Medical treatment is the primary option for patients with liver cancer, especially with advanced extrahepatic metastases. Molecular targeted therapy exerts an anti-tumor effect by acting on various signaling pathways involved in molecular pathogenesis; however, high drug resistance and low therapeutic responsiveness of PLC to molecular targets challenge the treatment option. In recent years, after surgical intervention, radiotherapy, chemotherapy, and/or molecular targeted therapy, autologous cell immunotherapy has been adopted for PLC. As a typical autologous cell immunotherapy, CAR T-cell therapy uses genetically modified T cells to express tumor-specific chimeric antigen receptors (CARs). Its targeting ability, persistent nature, and tumor-killing function result in a significant impact on the treatment of hematological tumors. However, no breakthrough has happened in the research specific to the curation of lung cancer, liver cancer, breast cancer, and other common solid tumors. In this context, a combination of molecular targeted therapy and CAR T-cell therapy was used to treat a patient with advanced HCC to achieve partial remission and facilitate further liver transplantation.